MOULDING THE ‘FEMME FATALE’ IN BLACK SWAN: A STUDY IN FEMINIST FILM THEORY صياغة صورة الامرأة القاتلة في البجعة السوداء (دراسة في نظرية الفلم النسوية) - Hadeel Aziz Muhammed هديل عزيز محمد رضا (Journal Of Babylon Center For Humanities Studies)
Feminism is quite known to the academic reader, however, involving it with relatively new forms of literature, such as film, may sound alarming. Film is indeed a popular form of literature that reflects modern life. The message it carries affects a very wide range of audience. It provides a new variety of technique (such as the I-Camera) and simultaneously employs the well-established standards of classic literature. This paper analyses Black Swan according to Feminist Film Theory. The analysis focuses on the portrayal of the heroine, Nina Sayers, especially her transformation into the Black Swan. The transformation is highly symbolic and, thus, it is achieved through many motifs and techniques, which will all be discussed throughout the paper. على الرغم من شهرة الحركة النسوية لدى القارئ الاكاديمي إلا ان ربطها مع احد الفنون الادبية الجديدة نوعا ما قد يبدو مثيرا للجدل. دخلت الأفلام الى ميدان الادب حديثا لتعبر عن مكنونات الحياة الحديثة وتؤثر من خلال الرسالة التي تحملها على الملايين من متابعيها بطريقة عجزت عنها الفنون الادبية الكلاسيكية. وذلك لكونها توظف التقنيات الحديثة دون المساس بالمعايير الادبية الكلاسيكية. يتناول هذا البحث تحليل البجعة السوداء باستخدام النظرية السينمائية النسوية التي تهتم بشكل خاص بتصوير الانثى. تخضع البطلة نينا سيرز الى سلسلة من التحولات البطيئة التي تتوج في النهاية بنجاح مسخ البطلة الى بجعة سوداء. تمتاز تلك التحولات برمزيتها وغموضها لذلك فإنها تتطلب توظيف التقنيات والموتيفات خلال العرض للوصول الى تلك الغاية.